UNDIFFERENTIATED SPONDYLOARTROPATHY: A CASE REPORT - Saime Sarıoğlu Ay; Burçin Aslan Özçakar; Gülay Dinçer (Archives of Rheumatology, 2003)
Undifferentiated spondyloarthropathies (uSpA) represent a group of patients with clinical and radiographic features suggestive of a seronegative spondyloarthropathy but not fulfilling the diagnostic criteria for any of the established diseases (ankylosing spondylitis, psoriatic arthritis, reactive arthritis, enteropathic arthtitis) in this group. Undifferentiated spondyloarthropathy is one of the common disease subset in the spectrum of seronegative SpA. Since uSpa may gradually develop definite SpA, systematic follow up is recommended. In this case, we present a 27-year-old man who fulfilled the European spondyloarthropathy Study Group (ESSG) criteria for seronegative spondyloarthropathies but not meet criteria for any of the disease and diagnosed as uSpA.